Combining Metaheuristics and Integer Linear Programming: A Hybrid Methodology Applied to the Container Loading Problem - Nepomuceno, Napoleão V.; Pinheiro, Plácido R.; Coelho, André L. V. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2007)
This paper presents a hybrid framework for coping with hard combinatorial optimization problems, which is based upon a methodology combining heuristic and exact methods. In this framework, a metaheuristic engine works as a generator of reduced instances for the problem, which are formulated as mathematical programming models. These instances, in turn, are solved by an exact optimization technique, and the performance measures accomplished by the respective models are interpreted as score values by the metaheuristic, thus guiding its search process. As a means to assess the potentialities behind the novel approach, we provide an instantiation of the framework to deal specifically with the container loading problem.